The potential of propolis extract gel Kabanjahe Kelulut bee as an anti-inflammatory agent in periodontal treatment: eksperimental laboratory study - Wulandari, Pitu; Maharani, Julia; Zulhendri, Felix; Lesmana, Ronny; Simanungkalit, Jayne Mary; Aulina, Datin Zahira (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Periodontitis treatment includes scaling and root planing, which can be supplemented with additional therapy, such as the administration of propolis. Propolis, a potential local natural resource, contains active metabolites that act as anti-inflammatory agents in periodontal healing. This study aims to analyze the effectiveness of propolis extract gel from Kelulut (stingless bees) as an anti-inflammatory agent in periodontal treatment. Methods: This laboratory-based experimental research employed a post-test-only control group design, divided into five groups: 50%; 60%; 70% propolis extract gel; Metronidazole Gel and Placebo Gel. The anti-inflammatory test was conducted using 50 male Wistar rats induced with periodontitis through silk ligature and P.gingivalis bacteria. The rats were sacrificed on the third and seventh days after treatment, and macrophage cells count were performed under a microscope at 400x magnification using Haematoxylin-Eosin staining. Results: The ANOVA test results showed no significant differences in the macrophage cells counts among the treatment groups on day 3 and day 7 in the periodontitis-induced rat model (p>0.05). The anti-inflammatory test results indicated a decrease in the mean macrophage cells count in each group by day 7. Conclusion: The use of Kelulut propolis extract gel from Kabanjahe was effective in reducing the number of macrophages in periodontitis-induced rats, with the 70% propolis extract gel demonstrating the best anti-inflammatory effectiveness in periodontal treatment. Potensi gel ekstrak propolis lebah kelulut kabanjahe sebagai agen anti inflamasi pada perawatan periodontal: eksperimental laboratoris Pendahuluan: Perawatan periodontitis meliputi scaling dan root planing serta dapat didukung dengan terapi tambahan berupa pemberian propolis. Propolis merupakan salah satu sumber daya alam lokal yang potensial, mengandung metabolit aktif yang berperan sebagai zat anti-inflamasi dalam penyembuhan periodontal. Penelitian ini bertujuan untuk menganalisis efektivitas gel ekstrak propolis dari lebah Kelulut (stingless bees) sebagai anti-inflamasi pada perawatan periodontal. Metode: Penelitian eksperimental laboratoris ini memiliki desain post-test-only control group design yang dibagi ke dalam lima kelompok yaitu kelompok gel ekstrak propolis 50%; 60%; 70%, gel Metronidazole dan gel Placebo. Pengujian anti-inflamasi menggunakan 50 ekor tikus wistar jantan yang diinduksi periodontitis dengan ligatur Silk 3/0 dan bakteri P.gingivalis. Tikus dikorbankan pada hari ketiga dan hari ketujuh setelah perlakuan, kemudian dilakukan penghitungan sel makrofag dengan mikroskop pada perbesaran 400x dengan pewarnaan Haematoxylin-Eosin. Hasil: Hasil uji ANOVA, tidak terdapat perbedaan bermakna pada setiap kelompok perlakuan terhadap jumlah makrofag. sel pada hari ke-3 dan hari ke-7 pada model tikus periodontitis (p<0.05). Hasil uji anti-inflamasi menunjukkan adanya penurunan rerata jumlah sel makrofag pada masing-masing kelompok pada hari ke-7. Simpulan: Terdapat efektivitas penggunaan gel ekstrak propolis lebah Kelulut Kabanjahe terhadap jumlah makrofag pada tikus yang diinduksi periodontitis dan gel ekstrak propolis 70% memiliki efektivitas terbaik sebagai anti-inflamasi pada perawatan periodontal.